Evaluation of Colistin Performance of Phoenix M50 with Sensitivity to FRCOL in Clinical Isolates - Ayşe Nur Ceylan; Selda Kömeç; Abdurrahman Gülmez; Beyza Öncel (Cam & Sakura Medical Journal, 2023)
Objective: In the report published by the Clinical Laboratory Standards Institute-European Committee on Antimicrobial Susceptibility Testing (EUCAST), Polymyxin Breakpoints Working Group, they recommended that laboratories using semi-automatic devices take into account the manufacturer's recommendations and implement strict quality control (QC) studies when reporting the colistin result. In this study, we compared the one-year colistin susceptibility results with those of Sensititre FRCOL and Phoenix M50. Thus, we aimed to determine the reliability of Phoenix M50 for reporting colistin results. Material and Methods: Extensively drug-resistant Gram-negative bacteria grown from clinical samples that arrived at the laboratory between June 2021 and June 2022 were included. MALDI- TOF Microflex LT/ SH Smart MS was used for bacterial identification, and Phoenix M50 and Sensititre FRCOL were used for colistin antibiotic susceptibility testing, according to the manufacturer's recommendations. The results obtained were evaluated in line with the EUCAST criteria. QC was performed using Escherichia coli ATCC 25922 and NCTC 13846 strains in accordance with EUCAST recommendations. Results: We studied 782 strains of K. pneumoniae (n=175), P. aeruginosa (n=99), and A. baumannii (n=508). Categorical agreements were 90.3%, 93.9%, and 94.5%. The very major error rate (VME) of Phoenix M50 was found to be 40.4%. Considering the VME for K. pneumoniae, A. baumannii, and P. aeruginosa, 17.7%, 75.0%, and 100.0% were found, respectively. The ME rates of K. pneumoniae, A. baumannii, and P. aeruginosa were 5.3%, 0.8%, and 1.1%, respectively. Conclusion: The susceptible colistin results of these bacteria by Phoenix M50 should be confirmed by broth microdilution as the VME is above acceptable values. While the results of colistin detection resistant by Phoenix M50 could be reported for P. aeruginosa and A. baumannii, it needs to be confirmed with broth microdilution for K. pneumoniae.